The development of an intelligent game-based system for learning sign language with kinect - Teerawat Kamnardsiri (2018)
© The Authors, 2016. All Rights Reserved. Sign Language (SL) is not a universal language, but diverse sign languages have been used in several countries, such as the UK, the US and Thailand. Sign Language is a visual language for communication between people with hearing impairment in everyday life. Nonetheless, standard sign language experts are rare and there is a lack of experts in the specification of standard sign languages. In this paper, we present the development of an intelligent game-based system for learning sign language with Kinect aiming at the practice of sign language for students with hearing impairment. The game-based learning provided learning activities that could suggest students to achieve an end goal. Moreover, knowledge capturing was employed by the knowledge engineering method from three sign language experts, as well as an action of sign language. After further analysis, immediate feedback and suggestions based on knowledge transfer from American Sign Language (ALS) experts were given. This experimental divided the students (N=31) into two groups. Group A (N=17) learnt with game-based learning while Group B (N=14) learnt with traditional face to face learning. As a result, this study provided a significant difference (p < 0.05) on the mean score of the post-test of both Group A as well as Group B. The final result showed that the game-based learning approach provides a performance of ASL vocabularies higher than the traditional face to face learning approach.